Visualization of Spatial Data Structures on Different Levels of Abstraction - Nikander, Jussi; Korhonen, Ari; Valanto, Eiri; Virrantaus, Kirsi (Electronic notes in theoretical computer science, 2007)
Spatial data structures are used to manipulate location data. The visualization of such structures faces many challenges that are not relevant in the visualization of one-dimensional data. The visualized data can be represented using several different types of visual metaphors. These metaphors can be divided into several different levels of abstraction depending on the purpose of the visualization. This paper proposes a division of data structure visualization into four levels of abstraction, and shows how these abstractions can be taken into account in the visualization of spatial data structures.